2020
DOI: 10.1021/acschemneuro.0c00348
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Functional Evaluation of a Novel Series of Phosphonate-Functionalized 1,2,3-Triazoles as Positive Allosteric Modulators of α7 Nicotinic Acetylcholine Receptors

Abstract: The α7 nicotinic acetylcholine receptor is a pentameric ligand-gated ion channel widely distributed in the central nervous system, mainly in the hippocampus and cortex. The enhancement of its activity by positive allosteric modulators (PAMs) is a promising therapeutic strategy for cognitive deficits and neurodegenerative disorders. With the aim of developing novel scaffolds with PAM activity, we designed and synthesized a series of phosphonate-functionalized 1,4-disubstituted 1,2,3-triazoles using supported co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
6
4
Order By: Relevance
“…The magnitude of the increase of the burst duration is more similar to that observed in the presence of low-efficacy type I PAMs, such as 5-HI, than in the presence of the highly efficacious type II PAMs, such as PNU-120596. In contrast to what we detected for other PAMs, such as 5-HI, 52 flavonoids, 13 and phosphonate-functionalized 1,4-disubstituted 1,2,3-triazole compounds, 56 the open state or that it does not exert any effect on desensitization, as expected for a type I PAM, since desensitization is the major determinant of α7 nAChR open channel lifetime. 53,57 Increasing the concentration of ligand 6 to 60 μM led to significantly reduced channel activity, with patches showing very low activity that did not allow further analysis (n = 11, N = 4), thus indicating an additional inhibitory effect.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the increase of the burst duration is more similar to that observed in the presence of low-efficacy type I PAMs, such as 5-HI, than in the presence of the highly efficacious type II PAMs, such as PNU-120596. In contrast to what we detected for other PAMs, such as 5-HI, 52 flavonoids, 13 and phosphonate-functionalized 1,4-disubstituted 1,2,3-triazole compounds, 56 the open state or that it does not exert any effect on desensitization, as expected for a type I PAM, since desensitization is the major determinant of α7 nAChR open channel lifetime. 53,57 Increasing the concentration of ligand 6 to 60 μM led to significantly reduced channel activity, with patches showing very low activity that did not allow further analysis (n = 11, N = 4), thus indicating an additional inhibitory effect.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
“…The magnitude of the increase of the burst duration is more similar to that observed in the presence of low-efficacy type I PAMs, such as 5-HI, than in the presence of the highly efficacious type II PAMs, such as PNU-120596. In contrast to what we detected for other PAMs, such as 5-HI, flavonoids, and phosphonate-functionalized 1,4-disubstituted 1,2,3-triazole compounds, ligand 6 did not increase open duration. This may indicate either that it has a very low efficacy to stabilize the open state or that it does not exert any effect on desensitization, as expected for a type I PAM, since desensitization is the major determinant of α7 nAChR open channel lifetime. , …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that α7nAChRs modulate nociceptive responses (Hone and McIntosh 2018), with positive allosteric modulators decreasing injury-induced hypersensitivity (Freitas et al 2013, El Nebrisi et al 2018, Nielsen et al 2020). The next set of experiments aimed at testing the hypothesis that 4R-mediated increases in cholinergic signaling lead to decreases in injury-induced hypersensitivity in male mice.…”
Section: Resultsmentioning
confidence: 99%
“…The particular form of the 1,2,3-triazole therapeutic agent that detects a specific biological target with dipole interactions and hydrogen bond is shown in Figure 3 . Protease inhibitors bind to a viral enzyme thereby precluding pathogen from replicating making agents such as 1,2,3-triazoles particularly suitable for use as a therapeutic agent that exhibits antiviral activities and pharmacophore biological properties against allergy [ 24 ].…”
Section: Ionic Liquid Sensingmentioning
confidence: 99%